Physiological Degradation of Pectin in Papaya Cell Walls: Release of Long Chains Galacturonans Derived from Insoluble Fractions during Postharvest Fruit Ripening - Prado, Samira B. R. do; Melfi, Paulo R.; Castro-Alves, Victor C.; Broetto, Sabrina G.; Araújo, Elias S.; Nascimento, João R. O. do; Fabi, João P. (Frontiers in Plant Science, 2016)
Papaya (Carica papaya L.) is a fleshy fruit that presents a rapid pulp softening during ripening. However, the timeline on how papaya pectinases act in polysaccharide solubilization and the consequent modification of the cell wall fractions during ripening is still not clear. In this work, the gene expression correlations between, on one hand, 16 enzymes potentially acting during papaya cell wall disassembling and, on the other hand, the monosaccharide composition of cell wall fractions during papaya ripening were evaluated. In order to explain differences in the ripening of papaya samplings, the molecular mass distribution of polysaccharides from water-soluble and oxalate-soluble fractions (WSF and OSF, respectively), as well as the oligosaccharide profiling from the WSF fraction, were evaluated by high performance size exclusion chromatography coupled to a refractive index detector (HPSEC-RID) and high performance anion-exchange chromatography coupled to pulse amperometric detection (HPAEC-PAD) analyses, respectively. Results showed that up-regulated polygalacturonase and β-galactosidase genes were positively correlated with some monosaccharide profiles. In addition, an overall increase in the retention time of high molecular weight (HMW) and low molecular weight (LMW) polysaccharides in WSF and OSF was shown. The apparent disappearance of one HMW peak of the OSF may result from the conversion of pectin that were crosslinked with calcium into more soluble forms through the action of PGs, which would increase the solubilization of polysaccharides by lowering their molecular weight. Thus, the results allowed us to propose a detailed process of papaya cell wall disassembling that would affect sensorial properties and post-harvesting losses of this commercially important fruit.